Evaluasi Tata Letak Fasilitas Kandang Pada Barokah Farm Dengan Pendekatan Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Rahman, Reindra; Herlinawati, Agtris; Ivana, Angela; Ramdhaniyah, Nadya; Prameswara, Dhita Icha; Hidayat, Agung Prayudha; Safitri, Astiani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Barokah Farm is a farm that focuses on fattening cattle but also raising dairy cattle. An important part of retail operations is the layout of the required areas separately such as sheds, wet food areas, dry food areas, milk packaging areas, equipment storage areas, offices, parking lots, etc. We chose Barokah Farm as a research subject to study and evaluate whether the flow of activities between facilities is effective. The aim of this research is to test and validate the layout of Barokah Farm using the Activity Relationship Diagram (ARC) and Total Closeness Rating (TCR) techniques. Based on the results of the Activity Relationship Chart (ARC) calculation at Baroka Farm, the feeding area has the highest Total Closeness Rating (TCR) value, namely 194, so it is prioritized as the most important facility to be built. Therefore, it is important to position other areas that have a high A value towards the feeding area so that they are close together and easier to work with. Strategic layout increases the efficient use of office space, employees and other facilities. Implementing the right layout will help operations run more smoothly and serve consumers.